The effectiveness of regulatory maximum levels for fumonisin mycotoxins in commercial and subsistence maize crops in South Africa - Shephard, Gordon S.; Burger, Hester-Mari; Rheeder, John P.; Alberts, Johanna F.; Gelderblom, Wentzel C.A. (Food control, 2019)
The fumonisins are carcinogenic mycotoxins that have been implicated in various adverse human health effects. Recently, the Codex Alimentarius Commission set maximum levels (MLs) for fumonisin mycotoxins at 4000 μg/kg for raw maize and 2000 μg/kg for maize flour and maize meal and these have been incorporated into South African health regulations. The MLs are intended to be health protective such that fumonisin exposures will be below the provisional maximum tolerable daily intake (PMTDI) of fumonisin of 2 μg/kg body weight/day set by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). South Africa has an extensive commercial maize farming industry as well as a large subsistence farming population reliant on home-grown maize. The available data on fumonisin contamination levels indicates that these MLs are readily met by the commercial crop. However, the situation in subsistence farming areas such as in the Eastern Cape Province region is of concern. The daily consumption of large amounts of highly fumonisin-contaminated home-grown maize is of relevance mainly due to rudimentary milling, which is not subject to the reduction in mycotoxin contamination associated with commercial milling. Analysis of historical fumonisin data from the Eastern Cape region indicates that approximately 12.8% of raw maize and 25% of the rural locally produced flour would not meet the respective MLs of 4000 μg/kg ML and 2000 μg/kg. Further analysis shows that given the high maize intake levels of this population, only prohibitively low MLs for raw maize of around 100–300 μg/kg would be health protective for different age groups in this area. Based on this analysis, the lowering of fumonisin exposure in subsistence farmers requires an integrated approach and cannot be achieved purely by regulatory means. •Current MLs for fumonisins in maize readily met by commercial maize in South Africa.•These MLs not health protective for rural subsistence farming communities.•Health protective MLs for subsistence farmers lead to unacceptable crop rejections.•Regulatory approach cannot address fumonisin exposure in subsistence farming areas.